Anabolic vs. Equine Reproduction (Revista Sistemas de Producción Agroecológicos, 2023)
The use of anabolic agents in equines aims to improve weight gain, energy levels and muscle mass, especially in horses recovering from disease, surgery, overexertion, among others. Adverse effects on equine reproduction as a consequence of inadequate handling of these drugs should be taken into account. In mares it can generate ovarian dysfunction, alterations in the estrous cycle and development of masculine characteristics. On the other hand, in stallions it results in decreased testicular mass, alteration in sperm production and behavioral changes, which can be reversible or irreversible depending on the age, sex, route, dose and frequency of administration of the anabolic agent. This work compiles information on the effects of anabolic agents on equine reproduction, with the purpose of generating awareness on the use of these substances and creating prevention policies on the indiscriminate application of these drugs.
Keywords: Anabolic agents; Equine; Mare; Reproduction; Stallion